2014
DOI: 10.3928/1081597x-20140429-02
|View full text |Cite
|
Sign up to set email alerts
|

Current Options in the Management of Pellucid Marginal Degeneration

Abstract: Although little is understood about the etiology, pathophysiology, epidemiology, and genetics of PMD, new treatments are improving visual outcomes and reducing complications. Corneal collagen cross-linking is especially exciting because it halts disease progression. Combined treatments and improved screening could eliminate the need for surgical management in most cases of PMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 90 publications
(129 reference statements)
0
13
0
7
Order By: Relevance
“…42 Eyes with peripheral steepening with pellucid marginal corneal degeneration, however, may also benefit from cross-linking. 88, 106 There is likely more than preoperative keratometry or age that determines extreme outcomes. 48 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…42 Eyes with peripheral steepening with pellucid marginal corneal degeneration, however, may also benefit from cross-linking. 88, 106 There is likely more than preoperative keratometry or age that determines extreme outcomes. 48 …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[9][10][11] Toric IOLs can be implanted in either the anterior or the posterior chamber, either with or without natural lens extraction (toric phakic IOLs (PIOLs)), and allow for the correction of refractive error and astigmatism independent of cornea alterations. 3 Camoriano et al 12 recently reported improved visual acuity and astigmatism with toric PIOL implantation for PMD in 10 eyes with severe glare and halos requiring removal in only 1 eye.…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Management of affected patients depends on the level of visual disability and can be organized in structural, partial-thickness, fullthickness, and corneal-independent interventions. 3 Structural interventions include techniques designed to strengthen the structure of the corneal stroma, such as corneal collagen crosslinking (CXL), 4 or techniques designed to modify the curvature and the mechanical properties of the corneal stroma, such as intrastromal corneal ring segments (ICRS). 5 Partial-thickness techniques comprise interventions involving the removal of only the anterior layer of the abnormally thinned cornea, with partial cornea replacement or the removal of the total cornea preserving the host endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported to stop the progression of ectasia, and studies reported persistent effects up to 7 years after treatment [2, 3]. Corneal CXL was also used to manage iatrogenic ectasias [3], pellucid marginal degeneration [19], infectious keratitis [4] or even bullous keratopathy [20]. It is believed to delay or even avoid invasive surgical procedures such as corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%